2010
DOI: 10.5001/omj.2010.52
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor, Tissue Factor Pathway Inhibitor and Factor VII Activity in Cardiovascular Complicated Type 2 Diabetes Mellitus

Abstract: There was a correlation between high TF, TFPI plasma levels, FVIIa activity and cardiothrombotic complications in T2DM especially in the presence of high risk factors such as poor glycemic control, dyslipidemia and obesity. Future target therapy against TF may be beneficial for T2DM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 42 publications
4
23
1
Order By: Relevance
“…The studies by Chu et al (2011) and El-Hagracy et al (2010) and the current study confirmed the role of TF in microvascular diabetic complications. However, the results revealed an endothelial dysfunction instead of the procoagulant state.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The studies by Chu et al (2011) and El-Hagracy et al (2010) and the current study confirmed the role of TF in microvascular diabetic complications. However, the results revealed an endothelial dysfunction instead of the procoagulant state.…”
Section: Discussionsupporting
confidence: 66%
“…It was observed that TF could dependently be associated with age and independently with triglycerides and total cholesterol. An increased TF level with age was observed by El-Hagracy et al (2010), which confirms a higher risk of the hypercoagulable state or endothelium damage with age. However, an inverse relationship between TF and triglycerides and total cholesterol is problematic to explain on the basis of the present results, perhaps the patients' treatment might have had a strong influence on the outcomes.…”
Section: Discussionsupporting
confidence: 58%
“…This observation is consistent with the studies of Ay et al [10] and Darvall et al [11], which may indicate the activation of the coagulation system, leading to an increase in thrombin generation. El-Hagracy et al presented a positive correlation between TF and BMI, elevating thrombotic tendency [12].…”
Section: Discussionmentioning
confidence: 97%
“…Lipids have a strong affinity for binding TFPI. Lipoprotein-associated TFPI presents fewer anticoagulant properties than free TFPI [12,17]. On the other hand, an increase in the expression of pro-inflammatory adipocytokines stimulates the release of TF-PI [17].…”
Section: Discussionmentioning
confidence: 99%
“…be the result of endothelial damage or increased procoagulant activity of TF. 15 The analysis of TFPI depending on the JAK2 V617F mutation revealed differences in the activity of TFPI between the subgroups with and without the mutation. We found a significantly reduced TFPI activity in patients with ET with the JAK2 V617F mutation, compared with patients without the mutation.…”
Section: Abbreviations: Ns Nonsignificantmentioning
confidence: 99%